Pembelajaran Tematik - Moh. Muklis (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2012)
National education has a strategic role and is very important in developing ability and forming temper also dignified nation civilization in order to educate the nation. The national education also has a goal to the development of education participant potential for being human who believe and devotion for God Almighty, noble, health, knowledgeable, competent, creative and being democratic citizens, also responsible. Thematic learning is a form that creates an integrated learning, that will push the students involvement in studying, making students to be active involved in the learning process and creates a situation of problem solving as the students’need, in studying thematically the students will be able to learn and play with a high creativity. The thematic learning is developed besides to achieve the learning goal that had determined, it is hoped that students can increase the concept understanding they learned meaningfully, develop the skill of finding, processing, information utilization, develop a positive position, a good habit, and transcendent values that are needed in life, develop social skills such as cooperation, tolerance, communication, also appreciate others’opinion, increase passion in studying, choose the suitable activity as their interest and needs.